A honeycomb-cobweb inspired hierarchical core–shell structure design for electrospun silicon/carbon fibers as lithium-ion battery anodes. (March 2016) - Wu, Junxiong; Qin, Xianying; Miao, Cui; He, Yan-Bing; Liang, Gemeng; Zhou, Dong; Liu, Ming; Han, Cuiping; Li, Baohua; Kang, Feiyu
Abstract: The silicon/carbon (Si/C) hybrid fibers with a hierarchical core–shell structure are prepared by encapsulating Si nanoparticles in the interconnected hollow carbon fibers (Si@IHCFs) based on a dual coaxial electrospinning technique. For the hierarchical structure, Si nanoparticles are embedded in the honeycomb-like carbon framework in the fiber core, which is further wrapped by the interlocked cobweb-like carbon shell network. As lithium-ion battery anode, the well-defined Si@IHCFs demonstrates a reversible capacity of 903 mAh g −1 and a capacity retention of 89% after 100 cycles with a current density of 0.2 A g −1 . With the current density gradually increasing to 2.0 A g −1, the electrode shows a specific capacity of 743 mAh g −1, exhibiting superior rate capability compared to the Si/C fibers with a core–shell but unconnected structure. The excellent electrochemical properties are attributed to the hierarchical core–shell structure and cross-linked network for the Si/C composite fibers. The carbon framework in the core region accommodates the volume expansion of Si by the honeycomb-like pores. And the interconnected carbon shell can not only prevent electrolyte from permeating into the core section, but also improve the electronic conductivity by the connections in the fiber network.